2005
DOI: 10.1007/bf02702022
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoceanographic implications of abundance and mean proloculus diameter of benthic foraminiferal speciesEpistominella exigua in sub-surface sediments from distal Bay of Bengal fan

Abstract: Temporal variation in abundance and mean proloculus diameter of the benthic foraminiferal species Epistominella exigua has been reconstructed over the last ∼ 50,000 yr BP, from a core collected from the distal Bay of Bengal fan, to assess its potential application in palaeoceanographic reconstruction studies. The down-core variation shows significant change in abundance of E. exigua during the last ∼ 50,000 yr BP. In view of the present day abundance of this species from areas with strong seasonal organic matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 23 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…a large proloculus at organic pollution (i.e. high food supply) [ 73 ], optimal growth and high food availability [ 74 ], and temperature and salinity [ 75 , 76 ]. As such, an extensive study of the plasticity of proloculus sizes in modern foraminifers would be timely.…”
Section: Discussionmentioning
confidence: 99%
“…a large proloculus at organic pollution (i.e. high food supply) [ 73 ], optimal growth and high food availability [ 74 ], and temperature and salinity [ 75 , 76 ]. As such, an extensive study of the plasticity of proloculus sizes in modern foraminifers would be timely.…”
Section: Discussionmentioning
confidence: 99%
“…The previous work on foraminiferal distribution along the beaches and the estuaries adjoining the Bay of Bengal was initiated by Ghosh (1966) and followed by various researchers (Bhalla 1968;Ghosh and Bhattacharjee 1993; see Khare et al 2007 for a comprehensive review). Foraminifera from the Bay of Bengal have also been used to reconstruct paleomonsoon (Cullen and Duplessy 1979;Cullen 1981;Duplessy 1982;Saraswat et al 2005;Rana and Nigam 2009;Panchang and Nigam 2012). Even though, extensive studies to document benthic foraminiferal distribution have been carried out along the east coast of India, no detailed study has yet been carried out to document recent benthic foraminiferal distribution and their ecological preferences from continental shelf region off Ganga-Brahmaputra-Mahanadi region.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have proposed a paleoclimate proxy based on proloculus sizes, suggesting that mean proloculus size decreases with warming seawater temperature and increasing salinity (Nigam 1986; Nigam and Rao 1987; Nigam and Khare 1995; Saraswat et al 2005). These studies calculated the mean proloculus size of a population using both microspheric and megalospheric forms; thus, a decrease in mean proloculus size reflects a greater proportion of microspheric forms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of within-species biogeographic variation in proloculus sizes of megalospheric forms also suggest that the environment underlies proloculus size distributions (Myers 1943; Eder et al 2016), but the environmental variable(s) shaping these patterns has not been identified nor have these patterns been quantified (see Beavington-Penney and Racey 2004). Furthermore, others have proposed that previously documented patterns of within-species proloculus size change might reflect the mixing of megalospheric and microspheric individuals (Röttger et al 1980; Racey 2001; Beavington-Penney and Racey 2004), because it can be difficult to differentiate between the two forms (e.g., Nigam and Khare 1995; Saraswat et al 2005). Herein, our results suggest that among-species patterns of megalospheric proloculus sizes are not constrained by the local environment, and consequently, ancient environmental conditions cannot be inferred from the study of fossil foraminiferal proloculus sizes alone.…”
Section: Discussionmentioning
confidence: 99%